An Odd End: Cambridge, Jesus College, MS Q.G.13, fol. 41a. (2nd December 2021) - Hanna, Ralph
Abstract: This note addresses a small obscurity in M. R. James's description of a manuscript at Jesus College, Cambridge. While the difficulty resolved is minor, it does gesture toward a persisting problem of manuscript production, how to conclude a book or similar smaller unit.